Gambaran Self Disclosure pada Remaja Pengguna Aplikasi Tiktok - Cut Miftahul Farrah; Yara Andita Anastasya; Rini Julistia (Humanitas (Jurnal Psikologi), 2023)
This study aims to determine the description of self-disclosure in adolescents who use the TikTok application. This research uses a quantitative approach with a descriptive type. The analysis used in this study is a univariate analysis. The sampling technique used non-probability sampling technique, namely snowball sampling, the number of respondents in this study was one hundred and ten people. The results of the study show that the highest level of self-disclosure is in the aspect of Determination & Honesty, then the description of the highest level of self-disclosure based on age is found in late adolescents aged twenty-one years. Then the description of the highest self-disclosure based on gender is found in  female sex so that the description of the highest level of self-disclosure based on opening the TikTok application is more or less five times, but the description of the highest level of self-disclosure based on the duration is one to two hours, and music content. It can be concluded that late adolescents who use the TikTok application often make self-disclosure and can provide self-information to others on social media.